UPAYA PENINGKATAN KETERSEDIAAN BIBIT JATI LOKAL Tectona grandis L.F PADA WILAYAH BERIKLIM KERING MELALUI PERBANYAKAN DENGAN STEK PUCUK YANG DIBERI BEBERAPA KONSENTRASI ZPT ROOTON-F - Aminuddin Mane Kandari; Asrianti Arif; Feliciano Soares (Jurnal Ecogreen, 2015)
The research of seedling multiplication on local species through the use of shoot cuttings given by Rooton-F PGR in a properly concentration has been implemented as one of the efforts to increase the availability of seedling. This is needed in order to develop a teak forest in the dry areas. The main objective of this study was to determine the properly Rooton-F concentration which showed the best effect on the growth of local teak shoot cuttings in the nursery. The research carried out at the home community nursery and continued in laboratory of forestry, Faculty of Forestry and Environmental Sciences, University of Halu Oleo for three months, from May to July 2015. The research method used completely randomized design (CRD), consists of six concentrate treatments on PGR Rooton-F, namely:  0 ppm as the control (A), 100 ppm (B), 200 ppm (C), 300 ppm (D), 400 ppm (E), 500 ppm (F) and 600 ppm (G).  The each treatment was repeated three times so that there were 18 units of research experiments. Results of the study were measured at the end of the study (46 HST) including: (1) the percentage of cuttings of life, (2) the length of roots, (3) root dry weight, (4) stem dry weight, (5) dry weight of shoots, (6) plant height, (7) and number of leaves. Analysis of the research data to determine the effect of treatment using the F test, while to know the different effects of each treatment used HSD test at the level of 95%. The results showed that Rotoone-F PGR significantly affect the growth of local teak shoot cuttings. The best concentration which gave the best growth in all measured variables was 300 ppm Rooton-F. Thus, propagation techniques in order to increase local teak seedling availability in the dry areas are suggested using shoot cuttings with Rooton-F concentration of 300 ppm. Keywords: Vegetative propagation, shoots cuttings, Rootone-F, Local Teak, Dry Climate